ANALISIS KELAYAKAN DAN PENGEMBANGAN USAHA LAUNDRY: Studi Kasus di Laundry XYZ Cinere - Danilo Generius Manalu (2023)
Laundry XYZ is a laundry business shop located on the side of the road on Jalan Raya Cinere. The large number of people's needs for laundry makes the laundry business increase and there is more competition. In addition, the owner of the XYZ laundry business also wants to see future prospects whether it is feasible to continue and develop or not. XYZ Laundry wants to open a branch if this business is feasible to continue and develop. To determine whether XYZ's laundry business is feasible or not, a thorough business feasibility analysis is needed. This analysis involves examining various financial metrics including NPV, PP, PI, and IRR as well as sensitivity analysis under three conditions: optimistic, best, and pessimistic. In addition, non-financial factors such as market analysis, marketing strategy and environmental considerations are taken into account. The results of both financial and non-financial analysis are then used to determine the feasibility of a business where XYZ laundry is feasible to be continued and developed. The results of the Financial Analysis conclude that the XYZ Laundry Business is not feasible. In the sensitivity analysis, optimistic conditions are not feasible because the PP results are far from what was determined. The pessimistic condition is not feasible because it does not fulfill the four conditions. The best condition is feasible because it meets all the conditions. The non-financial analysis results conclude that the XYZ Laundry Business is feasible.